Avoiding taxes by transfers within the family - Edoardo Di Porto; Henry Ohlsson (Uppsala University, Department of Economics, 2016)
We document an episode with considerable tax avoidance that occurred in Italy after 2008 when the Italian government reformed the property taxation by abolishing taxation on principal residences and increasing taxation on secondary properties. In presence of a very low inter vivos gift tax, Italian families found it beneficial to redistribute properties among their members. Difference-in-difference estimates indicate that property tax reform increased the probability that high-wealth donors made an inter vivos property gift by 3 percentage points and the size transferred by 4 square meters relative to less wealthy donors. Our estimates allow us to compute (back of the envelope) the amount of tax avoidance due to inter vivos transfer. The amount is around 78 million euros, or 4 percent of the annual tax revenue from principal residences.
urn:nbn:se:uu:diva-281769
Keywords: H27; D31; D11; 330; tax avoidance; property taxes; inter vivos gifts